Assessing the Need for Google Sites-Based Learning Media to Enhance Elementary Students’ Conceptual Understanding in Science Learning - Indra Budiman; Ayu Puji Rahayu; Suyato Kusumaryono; Fitri Eka Silviani; Mukhtiar Hussain Ibupoto (Education and Sociedad Journal, 2026)
This study aims to analyze the need for developing Google Sites-based learning media integrated with the Discovery Learning approach to improve elementary school students' problem-solving skills in science learning. This paper is important because science learning practices in elementary schools are still dominated by teachers and rely on limited interactive learning media, resulting in low conceptual understanding and limited opportunities for students to develop higher-order thinking and problem-solving skills. This study uses a descriptive mixed-methods approach by combining qualitative and quantitative data. Data were collected through classroom observations, interviews with teachers and students, student needs questionnaires, and analysis of learning documents and analyzed using a thematic approach. The research findings revealed that students experience difficulties in understanding abstract science concepts, especially photosynthesis, and tend to rely on memorization rather than conceptual understanding. Existing learning media are still limited, less interactive, and do not optimally facilitate student-centered learning. Quantitative results indicate that most students need digital learning media that are interactive, visual, easily accessible, and able to support the process of independent exploration and discovery. This study provides an empirical basis for designing innovative digital learning media using Google Sites to support the implementation of the Independent Curriculum and improve the quality of elementary science education.